Analisis Keamanan Nasional atas Kebijakan War on Drugs Presiden Duterte di Filipina - Pranawa Putra, I Gusti Ngurah Aristya; Resen, Putu Titah Kawitri; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2023)
This study aims to look at the reasons for the Philippines to continue implementing the War on Drugs policy, despite receiving criticism from the international community regarding human rights violations. This study used qualitative research methods. The rFesearcher uses the Realism and National Security framework to see the causality of the Philippines' attitude in responding to these pressures. In this study, it was found that the answer is that the increasing level of drug abuse in the Philippines has made the issue a threat to the Philippines' national security. The Philippines issued a War on Drugs policy to eliminate this threat, plus drug abuse has a close relationship with several crimes that threaten the safety of Filipinos. With this policy, the Philippines responds to international pressure by continuing to implement a drugs war policy because the Philippines still wants to maintain its national interests, namely the security of Filipino citizens. Keywords: National Security, Philippines, Realism, War on Drugs